Nature vs Enlightenment: Romanticism Analysis of William Wordsworth Poem “The World Is Too Much with Us” - Muajiz Muallim (Journal Corner of Education, Linguistics, and Literature, 2022)
Romanticism is not just a term that marks a certain period in western European society, it is also reflected in the works of literature in the 18th century and emerged as a movement, understanding, value, thought, freedom, morals, nature, art and literature. Thus, the aim of this research is to find how nature as the one of romanticism value reflected in William Wordsworth’s poem “The World is Too Much with Us”. In this research, the writer used a qualitative approach in collecting data and descriptive method in analyzing the data. The aim of this method is to describe the state of a situation in a systematic and factual manner. This makes it easier to understand the meaning of dictions, idioms and topics Finally, the William Wordsworth’s “The World is Too Much with Us “shows us how the element of nature found inside the poem. It is the author's way of contrasting the ideas of Romanticism over the materialistic society which is the product of the Enlightenment.